PERANCANGAN MEDIA INFORMASI PROMOSI TOEKANG PHOTO MANTAN PHOTOGRAPHY BERBASIS WEB : Design;Media;Information;Promotion;Photography;Website. - Megawaty, Merti; Wiradinata, Eking (FORTECH (Journal of Information Technology), 2022)
TPM Photography currently still uses brochures, word of mouth and Instagram. The purpose of this research is to design TPM Photography information media that can be accessed easily without being limited by time and distance. The research method used by the author in the preparation of this thesis is to use the Waterfall method. The analytical tool used is Data Flow Diagram (DFD). The design of this website uses the PHP programming language, MySql database, and XAMPP. With the Design of Web-Based TPM Photography Promotional Information Media, it is hoped that it will make it easier to do promotions and can increase the number of orders for Photography services.